Η καινοτομία των βιολογικών καλλυντικών προϊόντων και η αποδοχή τους από τους Κύπριους καταναλωτές - Πολυκάρπου, Μαρία (Department of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2015)
This dissertation studies Cypriots consumer behavior about organic cosmetics.
Keywords: Organic cosmetics; Consumer behavior; Βιολογικά καλλυντικά; Καταναλωτική συμπεριφορά